Superior Sensing Properties of Black Phosphorus as Gas Sensors: A Case Study on the Volatile Organic Compounds. Issue 1 (18th October 2018) - Ou, Pengfei; Song, Pengfei; Liu, Xinyu; Song, Jun
Abstract: The unique structure and prominent properties of black phosphorus (BP) and its monolayer and multilayers in device applications have attracted significant attention to this elemental 2D material. In this study, a comprehensive evaluation of the candidacy of monolayer BP as a channel material for high‐performance volatile organic compound (VOC) sensors is conducted combining first‐principles density functional theory calculations and non‐equilibrium Green's function formalism. The adsorption configurations and energetics of several typical VOCs (ethanol, propionaldehyde, acetone, toluene, and hexane) on monolayer BP are examined and it is demonstrated that VOCs generally exhibit stronger interaction with monolayer BP than with the widely studied monolayer MoS2, indicative of monolayer BP potentially being a more sensitive VOC sensor. Monolayer BP is shown to exhibit highly anisotropic transport behaviors, whereas the absolute modification of current–voltage responses due to VOCs is found to show a trend that is direction independent. Moreover, the adsorption of VOCs on monolayer BP is strong enough to resist thermal disturbance, yet allows fast recovery time. The results suggest that BP is a compelling and feasible candidate for sensing applications of VOCs. Abstract : The candidacy of monolayer black phosphorus (BP) as a channel material for high‐performance volatile organic compound (VOC) sensors is evaluated. A strong interaction between VOCs and monolayer BP is demonstrated, leading to stable VOC adsorption that is strong enough to resist thermal disturbance, yet allows fast recovery. The results suggest BP as a compelling and feasible candidate in VOCs sensors.